Two novel compound heterozygous BMP1 mutations in a patient with osteogenesis imperfecta: A case report - Sangsin A. (2017)
© 2017 The Author(s). Background: Osteogenesis imperfecta (OI) is a collagen-related bone dysplasia leading to a susceptibility to fractures. OI can be caused by mutations in several genes including BMP1. It encodes two isoforms, bone morphogenetic protein 1 (BMP1) and mammalian tolloid (mTLD); both have proteolytic activity to remove the C-propeptide from procollagen. Case presentation: We report a Thai OI patient who had his first fracture at the age of three months. Using next generation sequencing, we successfully identified two novel compound heterozygous BMP1 mutations. One mutation, c.796_797delTT (p.Phe266Argfs*25) affects both BMP1 and mTLD isoforms, while the other, c.2108-2A > G, affects only the BMP1 isoform. Preservation of the mTLD may explain the relatively less severe clinical phenotype in this patient. Intravenous bisphosphonate was given from the age of 8 months to 5 years. He was free from fractures for 9 months before discontinuation. Conclusion: This case expands the mutation spectrum of BMP1, strengthens the correlation between genotype and phenotype, and supports the benefits of bisphosphonate in OI patients with BMP1 mutations.